Unusual dental symptoms in Tornwaldt cyst: A case report - Rasoul A.M.; Ibrahim N. (Penerbit Universiti Sains Malaysia, 2024)
Tornwaldt (Thornwaldt) or nasopharyngeal cyst is a cyst occurred at the connection site of pharyngeal endoderm and notochord remnant, usually located in the midline postero-superior wall of nasopharynx. Nasopharynx's obstruction, recurrent infection or trauma may exacerbate mucous secretion by the potential space lining. Although rare and is usually symptomless, it is not uncommon for the patients to have some nasal, ear, cervical or oral symptoms. We report a case of Tornwaldt cyst with rare associated dental symptoms. The patient's initial presentations were dry mouth, cheek biting, post nasal drip and few nasal symptoms including frequent snoring, sleep apnoea, mouth breathing, sneezing, sore throat and itchiness. These symptoms were tremendously and immediately relieved once the cyst was surgically removed. Penerbit Universiti Sains Malaysia. 2018.